2022
DOI: 10.1089/heq.2022.0063
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review: Impact of Social Determinants of Health on the Management and Prognosis of Gallstone Disease

Abstract: Background: Due to its prevalence, gallstone disease is a major public health issue. It affects diverse patient populations across various socioeconomic levels. Socioeconomic and geographic deprivation may impact both morbidity and mortality associated with digestive diseases, such as biliary tract disease. Aim: The aim of this systematic review was to review the available data on the impact of socioeconomic determinants and geographic factors on gallstone disease and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Research has indicated the presence of racial and ethnic discrepancies, revealing that African American and Hispanic communities exhibit a greater frequency of H. pylori infection compared to their White counterparts [ 13 ]. Likewise, areas characterized by impoverished living conditions and individuals facing economic hardship demonstrate a heightened occurrence of gallstone disease and other biliary disorders, highlighting the significant impact of socioeconomic elements on disease prevalence [ 14 , 15 ]. These revelations emphasize the imperative of confronting systemic racism, poverty, and inadequate healthcare accessibility to mitigate the disproportionate burden of H. pylori infection and biliary disease across diverse demographic and socioeconomic strata.…”
Section: Discussionmentioning
confidence: 99%
“…Research has indicated the presence of racial and ethnic discrepancies, revealing that African American and Hispanic communities exhibit a greater frequency of H. pylori infection compared to their White counterparts [ 13 ]. Likewise, areas characterized by impoverished living conditions and individuals facing economic hardship demonstrate a heightened occurrence of gallstone disease and other biliary disorders, highlighting the significant impact of socioeconomic elements on disease prevalence [ 14 , 15 ]. These revelations emphasize the imperative of confronting systemic racism, poverty, and inadequate healthcare accessibility to mitigate the disproportionate burden of H. pylori infection and biliary disease across diverse demographic and socioeconomic strata.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States and around the world, gallstone-related diseases like cholelithiasis and cholecystitis significantly contribute to morbidity and mortality rates, placing a substantial burden on healthcare resources [1]. Over 20 million people in the United States have been diagnosed with gallbladder disease through ultrasonographic evaluations [2].…”
Section: Introductionmentioning
confidence: 99%